Open surgical cholecystostomy under local anaesthesia as salvage therapy of acute cholecystitis during the 4th COVID-19 wave in Northern Italy: experience from a rural hospital - Montali, Filippo; Virgilio, Edoardo; Ballabeni, Lucia; Bignone, Maddalena; Rollo, Alessio; Costi, Renato (Acta Biomedica Atenei Parmensis, 2023)
The COVID-19 pandemic outbreak delayed interventions of elective surgery worldwide. In Italy, the first western country to be affected, 410000 operations formerly planned were cancelled with the beginning of the first wave. Symptomatic cholelithiasis represents one of the most common, benign medical conditions in the world leading the affected patients to general surgeons’attention; in 0.5% of cases gallstones (symptomatic or not) can complicate with acute lithiasic cholecystitis (ALC) whose universally acknowledged treatment of choice is laparoscopic cholecystectomy. Delaying in surgery of ALC can increase the rate of complications like severe ALC, acute cholangitis and sepsis. The 4th wave of COVID 19 in Northern Italy induced further stress on the healthcare system. In fact, the occurrence of difficult communication and delays in ALC patients transfer between first and second level hospitals lead to the re-emergence of obsolete surgical procedures. In our rural hospital, in fact, a 92 years old patient affected with ALC and several comorbidities was treated with a successful emergency surgical procedure of transperitoneal cholecistostomy in lieu of a radiological transperitoneal approach. Such a choice was dictated by the absence of an interventional radiology unit in our hospital as well as the unavailability of patient transfer to our central referral hub (the hospital of Parma) due to hospital overcrowding secondary to the 4th wave of COVID 19 pandemic.